Carbon Disclosure, Maturity, and Shareholder Value: Is It a Matter for the Board of Directors? - Erlynda Yuniarti Kasim; Ade Imam Muslim (Institut Bisnis dan Informatika Kesatuan, 2025)
Environmental transparency and corporate governance are increasingly important for enhancing shareholder value in manufacturing firms. This study aims to examine the impact of carbon disclosure, corporate maturity, and the presence of women on boards of directors and commissioners on shareholder value in manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. The objectives include assessing whether carbon disclosure and corporate maturity positively influence shareholder value, evaluating the moderating role of corporate maturity, and analyzing the effect of female board representation. The research employs a quantitative approach, using moderated regression analysis with panel data from 116 companies, resulting in 580 firm-year observations. The findings indicate that carbon disclosure positively affects shareholder value, suggesting that transparent environmental reporting attracts investor interest. Corporate maturity also has a positive impact and strengthens the relationship between carbon disclosure and shareholder value. However, the presence of women on boards does not significantly influence shareholder value, likely due to their low representation. The study concludes that companies should prioritize carbon disclosure and leverage corporate maturity to enhance investor confidence. Increasing female representation on boards may align with global governance trends, despite its limited impact in this context.